Pembiasaan Membaca Sholawat Busyro Setelah Apel Pagi Sebagai Upaya Menumbuhkan Karakter Religius Siswa MII Banyurip Ageng 02 Kota Pekalongan - Maulida, Ida Khikmatul; Prayogi, Arditya; Nasrullah, Riki; Setiawan, Singgih; A’yun, Qurrota (Khazanah : Journal of Islamic Studies, 2025)
Instilling religious values ??is a fundamental aspect of character education in elementary schools. This article discusses the implementation of the habit of reading Sholawat Busyro which is carried out after the morning assembly as an effort to foster the religious character of students at MII Banyurip Ageng 02 Pekalongan City. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The results of the study indicate that the habit of reading Sholawat Busyro is carried out routinely, spontaneously, and through exemplary behavior, and is followed by all students and teachers every morning. The implementation of this activity follows the steps: student training and mentoring, giving appreciation, strengthening morals through the knowing-feeling-doing approach, and avoiding criticism. This activity forms students' religious character such as humility, politeness, discipline in worship, and love for the Prophet. Supporting factors for this habit include teacher assertiveness, involvement of all students, a safe environment, and implementation of the habit as a mandatory madrasah activity. The inhibiting factors include students' inability to memorize, laziness in reciting Sholawat Busyro, limited time, and incorrect pronunciation. The results of this study recommend the habituation of sholawat as an effective strategy to form students' religious character comprehensively and applicatively in elementary education environments.